Moringa oleifera Seeds Extract Effervescent Tablets as Water Purifier: to Overcome Clean Water Issues - Rosda Rodhiyana; Siti Nur Fadillah (Konsorsium Ilmu Biomedik Indonesia (KIBI), 2022)
Background; Water quantity and quality are important determinants of health. However, this does not fit with the availability of clean water. Today, 771 million people in the world lack access to it. In Indonesia, only 84.91% of households have access to clean water. Moreover, with the COVID-19 pandemic, access to clean water becomes a vital part to eliminate the spread of the virus. Reviews; People usually treat groundwater, river water, and wastewater by adding inorganic coagulants, such as aluminium sulphate to meet this need. But these coagulants aren't completely safe for health and the environment. Aluminium sulphate could cause neurological disease and carcinogens. In the environment, it’s causing pollution since it's undegradable. Hence, alternative coagulants to overcome these problems should be considered. Among the plants that have shown coagulant effect is Moringa oleifera. Many researchers have shown that Moringa seeds can reduce water effluent by up to 80-99%. The seeds are biodegradable and safe for humans. However, the use of Moringa seeds as a coagulant is only in the form of dry powder without further formulation. Therefore, to maximize its activity as a coagulant, Moringa seeds need to be processed further by forming effervescent tablets. Conclusion; Effervescent tablets were chosen because they can dissolve quickly and evenly so that all active compounds of Moringa can work perfectly. This formulation is expected to increase the ability as a coagulant so that public access to clean water can increase. So, contributing to the Sustainable Development Goals (SDGs) number six, Clean Water and Sanitation. Keywords: Moringa oleifera, clean water, coagulant, effervescent, SDGs